Experimental economics applied to decision making in dynamic and complex environments: A review of designs and results (2009)
The article reviews the use of economics, psychology and business administration science laboratory experiments in the study of decision making in complex and dynamic environments. Such environments have not been sufficiently utilized in the laboratory, in spite of knowing that they greatly contribute to the external validation of experiments. In the ambit of economics, the results support, with some exceptions, the rational choice or perfect rationality theory; whereas in psychology and business administration sciences they support the limited rationality theory and the use of heuristics or mental shortcuts for making decisions. In general, it can be said that the complexity that people confront in dynamic environments compromises their rationality, which in turn has a negative effect on their decision making performance. The reviewed studies manifest the flexibility offered by experimental economics in designing laboratory trials, particularly those intended to test theories that are relevant in a large number of situations, especially in complex and dynamic environments.